FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSITAS PERENCANAAN STRATEGIK DAN KINERJA FINANSIAL PADA BANK PERKREDITAN RAKYAT DI JAWA TENGAH - Jumingan Jumingan (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2015)
This study aimed to examine the effect of managerial factors, the environment of the intensity of strategic planning; examine the influence of organizational factors on the intensity of strategic planning; mnguji influence of organizational factors on the financial performance; examine the effect of the intensity of strategic planning to financial performance. To test this research used structural equation model (SEM) whereas the use of the most fundamental measure of the overall fit is Likelhood ratio chi-square (x2) using seven steps in this modeling. The population in this study is the manager BPR Central Java, sample taken 182 respondents. Results of this study show: first that the intensity level of strategic planning is not determined by the skills, confidence and experience in developing strategic planning manager. Both the intensity of strategic planning is also affected by organizational factors BPR which include size, structural and centralization, meaning that the larger the size businesses BPR with structural complexity are higher and the degree of centralization of authority given to the manager, the lower the intensity did the manager in preparing the strategic planning. Third the larger size BPR business with higher structural complexity and the degree of centralization of authority given to the manager, it will obtain the level of the higher financial performance shown by the profits, the level of ROE and petumbuhan deposits.